2021
DOI: 10.1111/cob.12473
|View full text |Cite
|
Sign up to set email alerts
|

Understanding bariatric patients' experiences of self‐management post‐surgery: A qualitative study

Abstract: Summary Although most bariatric patients achieve significant weight loss and improvements in both physical and mental health‐related quality of life (HRQoL) in the short‐term, there is wide variability in weight and long‐term HRQoL outcomes. The role of bariatric patients' self‐management style in explaining variability in long‐term outcomes is unclear. This qualitative study examined bariatric patients' self‐management experiences after bariatric surgery in relation to long‐term outcomes. A qualitative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…As patients approach weight nadir, and rapid weight loss curtails, they enter the "the work begins" phase where their newly formed good habits must be maintained to avoid or minimize weight regain. 29,30,36 Specific habits facilitating weight loss maintenance include patients' actively interrogating the role of food in their life, identifying triggers for consumption, and establishing new relationships with food. 26,29,30,34 Conversely, patients blinded by "easy" weight loss failed to modify their food relationships 24,35 ; whereas, others learnt to actively subvert the limits of their bariatric surgery: "I found that if I chewed the food tremendously to a pulp I could actually get more of it quite frequently …."…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…As patients approach weight nadir, and rapid weight loss curtails, they enter the "the work begins" phase where their newly formed good habits must be maintained to avoid or minimize weight regain. 29,30,36 Specific habits facilitating weight loss maintenance include patients' actively interrogating the role of food in their life, identifying triggers for consumption, and establishing new relationships with food. 26,29,30,34 Conversely, patients blinded by "easy" weight loss failed to modify their food relationships 24,35 ; whereas, others learnt to actively subvert the limits of their bariatric surgery: "I found that if I chewed the food tremendously to a pulp I could actually get more of it quite frequently …."…”
Section: Synthesismentioning
confidence: 99%
“…34 This may be a contributing factor to patients who reported that challenging eating behaviors re-emerged as physical limitations on eating waned, resulting in difficulty maintaining weight loss. 28,30,33,35,36…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have assessed the lifelong adherence to healthy lifestyle after the surgery; and found that non-adherence with dietary recommendations/loss of dietary control and exercise recommendations were important causes for weight regain post-surgery [14,15] [16-18] [19]. Several studies have shown that self-management is the best approach to maintaining weight loss (WL) and preventing weight gain after bariatric surgery [20][21][22]. The critical components of self-management after bariatric surgery to maintain WL are healthy eating behaviors and regular physical activity [23,24].…”
Section: Introductionmentioning
confidence: 99%